2019
DOI: 10.1002/ejic.201900484
|View full text |Cite
|
Sign up to set email alerts
|

NHC‐Stabilized Nickel Olefin, Dialkyl, and Dicyanido Complexes

Abstract: The complexes trans-[Ni(iPr 2 Im) 2 Br 2 ] 1, trans-[Ni-(iPr 2 Im Me ) 2 Br 2 ] 2, trans-[Ni(Me 2 Im) 2 I 2 ] 3, and trans-[Ni-(Me 2 Im Me ) 2 Br 2 ] 4 (R 2 Im = 1,3-diorganyl-imidazolin-2-ylidene, R 2 Im Me = 1,3-diorganyl-4,5-dimethyl-imidazolin-2-ylidene) are useful precursor for the synthesis of NHC-stabilized nickel olefin, alkyne, alkyl and cyanido complexes. [Ni(NHC) 2 (η 2 -olefin)] and [Ni(NHC) 2 (η 2 -alkyne)] can be prepared via metallic reduction in the presence of the olefin or alkyne, as exemplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 54 publications
1
17
0
2
Order By: Relevance
“…In the 29 Si NMR spectrum, a resonance at 121.9 ppm also indicated the formation of a silylene transition metal complex. Two carbonyl stretching bands at 1971 and 2010 cm −1 were observed in the IR spectrum at rather low energies compared to other complexes of the type [Ni(CO) 3 (L)] . The X‐ray crystal structure (Figure ) of the product 2 revealed that the reaction of [Ni(CO) 4 ] with one equivalent of Dipp 2 NHSi leads to a dimeric, silylene‐bridged complex [{Ni(CO) 2 ( μ ‐Dipp 2 NHSi)} 2 ] 2 , which was, most probably, formed from the colorless intermediate [Ni(CO) 3 (Dipp 2 NHSi)] 1 (Scheme ) upon CO elimination and subsequent dimerization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 29 Si NMR spectrum, a resonance at 121.9 ppm also indicated the formation of a silylene transition metal complex. Two carbonyl stretching bands at 1971 and 2010 cm −1 were observed in the IR spectrum at rather low energies compared to other complexes of the type [Ni(CO) 3 (L)] . The X‐ray crystal structure (Figure ) of the product 2 revealed that the reaction of [Ni(CO) 4 ] with one equivalent of Dipp 2 NHSi leads to a dimeric, silylene‐bridged complex [{Ni(CO) 2 ( μ ‐Dipp 2 NHSi)} 2 ] 2 , which was, most probably, formed from the colorless intermediate [Ni(CO) 3 (Dipp 2 NHSi)] 1 (Scheme ) upon CO elimination and subsequent dimerization.…”
Section: Resultsmentioning
confidence: 99%
“…The X‐ray crystal structure (Figure ) of the product 2 revealed that the reaction of [Ni(CO) 4 ] with one equivalent of Dipp 2 NHSi leads to a dimeric, silylene‐bridged complex [{Ni(CO) 2 ( μ ‐Dipp 2 NHSi)} 2 ] 2 , which was, most probably, formed from the colorless intermediate [Ni(CO) 3 (Dipp 2 NHSi)] 1 (Scheme ) upon CO elimination and subsequent dimerization. The dimer is built from two [Ni(CO) 2 (Dipp 2 NHSi)] moieties, which are connected by a nickel–nickel bond (Ni1–Ni1’ 2.5218(5) Å) of a similar length to those in bridged dinuclear nickel complexes (2.36–2.54 Å) . The molecules lie on an inversion center located between the Ni atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LIFDI-Orbitrap applications became quite numerous but while the results presented in these publications are heavily relying on accurate mass data by LIFDI-Orbitrap, they generally do not show these spectra. [172][173][174][175][176][177][178][179] It is a general phenomenon that in the field of LIFDI-MS there are quite a number of custom solutions available that deliver good analytical results in routine use, while the exact setup of some of them has unfortunately never been published.…”
Section: Mass Analyzers For Fi Fd and Lifdimentioning
confidence: 99%
“…The best option to realize high-resolution accurate mass measurements in FI, FD or LIFDI mode is to combine them with mass analyzers that do not require internal calibration, which is the case with FT-ICR [59][60][61][62]141,142,[164][165][166][167][168] and Orbitrap systems. [172][173][174][175][176][177][178][179] Gas chromatography-field ionization-mass spectrometry Gas chromatography-field ionization (GC-FI) is the easiest to set up hyphenation within the FI/FD/ LIFDI family, because for the most part, it just means doing FI with sample introduction from a gas chromatograph, and therefore has been accomplished soon after the introduction of FI-MS. [221][222][223] In GC-FI, all parameters of the gas chromatographic separation that may have been established in EI mode can be used without any modification. Differences to EI are caused by much lower ion currents, and consequently, the strong need to optimize the ion yield.…”
Section: Accurate Mass Measurementsmentioning
confidence: 99%